Efektifitas Pembangunan Dua Rumah Sakit Umum Daerah di Kabupaten Seruyan Propinsi Kalimantan Tengah Tahun 2007 - Bahrun Abbas; Laksono Trisnantoro (Center for Health Policy and Management, 2014)
Background: In the current era of regional autonomy, local goverments have wider scope of authority in making their policies according to their capacities and their needs. To improve access to health care and equitable health service, the Goverment of Seruyan District made a policy to build two District Hospitals. This policy was made due to the area of Seruyan District that is very widespread. In its implementation, this policy has been confronted with many obstacles, among other is limited human resources and funding, and low utilization of health facilities and services by community. Objective: To determine the extent of utilization of the two hospitals and to determine the factors corresponding to the utilization of the two District Hospitals in Seruyan Districy. Metodhs: This study is a descriptive study with a qualitive approach supported by a quantitive approach. Hospital utilization data are obtained by examining the available data in both District Hospitals in Seruyan District and two other hospitals in the neighboring district, and also by interviewing some people in Seruyan District. Samples are determined using two stage cluster sampling. To further investigate the issue of hospital utilization, in-depth interviews are conducted both with people using the hospitals and with people not using the hospitals in Seruyan District. The data will be quantitatively analyzed and further explore qualitatively. Results: The result findings show that there is a correlation between the distances of home and hospital and seeking treatment at the hospital, there is a correlation between the means of transportation to the hospital and seeking treatment at the hospital, there is a correlation between travel time to the hospital and seeking treatment at the hospital, there is a correlation between the ease of transportation to the hospital and seeking treatment at the hospital, there is a correlation between cost of transportation to the hospital and seeking treatment at the hospital, there is no correlation between the expenses and seeking treatment at the hospital, and there is a correlation between people’s knowledge and seeking treatment at the hospital. Conclusion: In terms of its utilization and manpower, the construction of two hospitals in Seruyan District is ineffective. However, factors correlating with hospital utilization are distance, transportation, travel time, ease of transportation, transportation cost dan knowledge, and government should pay attention to these factors to improve utilization. Latar belakang: Dalam era otonomi daerah saat ini Pemerintah Daerah memiliki kewengan lebih luas dalam mengambil kebijakan yang sesuai dengan kemampuan dan kebutuhan daerah. Untuk meningkatkan akses pelayanan kesehatan, pemerataan pelayanan kesehatan maka Pemerintah Kabupaten Seruyan membuat kebijakan pembangunan 2 RSUD. Kebijakan ini diambil mengingat sangat luasnya wilayah Kabupaten Seruyan. Dalam pelaksanaannya kebijakan ini menghadapi berbagai kendala diantaranya, keterbatasan sumber daya manusia dan keterbatasan pembiayaan, serta masih rendahnya pemanfaatan sarana pelayanan kesehatan oleh masyarakat. Tujuan penelitian: Untuk mengetahui sejauh mana pemanfaatan 2 RSUD tersebut dan untuk mengetahui faktor- faktor yang berhubungan terhadap pemanfaatan 2 RSUD di Kabupaten Seruyan. Metode: Jenis penelitian ini adalah penelitian deskriptif dengan pendekatan kuantitatif didukung kualitatif. Data pemanfaatan rumah sakit dilakukan dengan menelaah data yang ada di kedua rumah sakit di Kabupaten Seruyan dan 2 rumah sakit Kabupaten tetangga, serta melakukan wawancara terhadap masyarakat Kabupaten Seruyan. Sampel ditentukan dengan metode two stage cluster sampling. Untuk lebih mengetahui permasalahan pemanfaatan rumah sakit dilakukan wawancara mendalam kepada masyarakat yang memanfaatkan rumah sakit umum daerah di Kabupaten Seruyan dan yang tidak memanfaatkan. Data akan dianalisis secara kuantitatif dan diperdalam dengan kualitatif. Hasil: Ada hubungan antara jarak rumah dengan berobat ke rumah sakit, ada hubungan antara sarana transportasi dengan berobat ke rumah sakit, ada hubungan antara waktu tempuh dengan berobat ke rumah sakit, ada hubungan antara kemudahan transportasi dengan berobat ke rumah sakit, ada hubungan antara biaya transportasi dengan berobat ke rumah sakit, tidak ada hubungan antara biaya pengeluaran dengan berobat ke rumah sakit dan ada hubungan antara pengetahuan masyarakat dengan berobat ke rumah sakit. Kesimpulan: Pembangunan 2 RSUD di Kabupaten Seruyan tidak efektif apabila dilihat dari segi pemanfaatan dan ketenagaan. Faktor yang berhubungan dengan pemanfaatan RSUD adalah jarak, sarana transportasi,waktu tempuh,kemudahan transportasi, biaya transportasi dan pengetahuan. Pemerintah perlu mengupayakan perbaikan dalam hal-hal di atas untuk meningkatkan utilisasi rumahsakit.